Financial Literacy, Digital Nomadism, and Fintech Payment on Consumptive Behavior: Self-Control as a Mediating Variable in Generation Z - Husnaeda; A. Ifayani Haanurat; Muhammad Nur Abdi (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the influence of financial literacy, digital nomadism, and fintech payment on the consumptive behavior of Generation Z, with self-control as a mediating variable. The research was conducted nationally across Indonesia involving 252 Generation Z respondents born between 1999 and 2012 who are active fintech payment users from over 50 cities. Data were collected through an online questionnaire using purposive and snowball sampling techniques, and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) via SmartPLS 4.0, grounded in the Theory of Planned Behavior and Self-Control Theory. The results indicate that financial literacy, digital nomadism, and fintech payment each positively and significantly influence both consumptive behavior and self-control among Generation Z. The most notable finding is that higher financial literacy is associated with greater consumptive behavior (β = 0.348). This occurs because a better understanding of digital financial products encourages individuals to transact more actively and confidently, ultimately increasing spending frequency rather than reducing it. Self-control was confirmed as a partial mediator across all three pathways, with the model explaining 43.9% of the variance in Generation Z consumptive behavior This study affirms that self-control plays a critical role as the mechanism bridging external factors and actual consumption behavior. Therefore, financial education programs should integrate self-control training beyond mere cognitive knowledge transfer to effectively translate financial literacy into responsible financial behavior.